2017
DOI: 10.1007/s10616-017-0163-7
|View full text |Cite
|
Sign up to set email alerts
|

PDGFR inhibition mediated intracellular signalling in C6 glioma growth and migration: role of ERK and ROCK pathway

Abstract: Aberrant PDGFR (Platelet derived growth factor receptor) signalling in brain tumors and gliomas is one of the primary cause of tumor progression. PDGFR stimulation by its ligand and the role of its downstream mediators such as extracellular regulated kinases (ERK1/2), PI3K and ROCK pathways have not been thoroughly investigated. The present study sought to investigate the role of PDGF receptor signalling inhibition on suppression of rat C6 glioma growth and migration. Treatment of C6 cells with PDGFR inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Therefore we hypothesized a possible cross-talk between Alcama and Pdgfr- α . It is known that PDGF signaling leads to an increase in AKT and ERK phosphorylation 34,35 . We firstly investigated the impact of alcama knock-down on pERK signaling in the caudal region at 26 hpf.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore we hypothesized a possible cross-talk between Alcama and Pdgfr- α . It is known that PDGF signaling leads to an increase in AKT and ERK phosphorylation 34,35 . We firstly investigated the impact of alcama knock-down on pERK signaling in the caudal region at 26 hpf.…”
Section: Resultsmentioning
confidence: 99%
“…Since the involvement of PI3K in SCP migration was revealed, we then mutated two tyrosine residues in the intracellular domain of Pdgfr-α that are responsible for the binding of class IA (α/ α/ δ) PI3K to Pdgfr- α following its activation and autophosphorylation 34 (Fig. 4A), and we cloned the mutated or WT pdgfra ORF followed by a tandem HA-tag downstream of a hsp70 promoter 38 (hsp70:pdgfra-ΔPI3K-HA or hsp70:pdgfra WT -HA, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of the RhoA target ROCK led to increased migration in glioma cells via an activation of Rac1 [507] and Rac1 inhibition was associated with reduced migration and invasion [507,508,509]. Contrasting these observations, other studies found ROCK inhibition associates with the reduced migration of glioma cells [510,511]. A possible explanation for this discrepancy might be due to biphasic effects of ROCK activity.…”
Section: Cytoskeletal Alterations In Gliomamentioning
confidence: 99%
“…In hepatocellular carcinoma, Sorafenib combined with vitamin K1 significantly inhibited the hepatocellular carcinoma cell migration through decreased ERK1/2 phosphorylation (D'Alessandro et al 2018). Furthermore, inhibition of the platelet-derived growth factor receptor resulted in an obvious suppression of migration and proliferation in glioma cells via regulation of the FAK/paxillinERK signaling pathway (Singh et al 2018).…”
Section: Discussionmentioning
confidence: 99%